Features of the distribution of the concentration on the mucous stomach of active and inactive forms of helicobacterial infection in patients with chronic non-atrophic gastritis, suffering and not suffering from chronic constipation - I. N. Shukhtina; A. A. Avramenko (Kazimierz Wielki University, 2019)
The frequency of detection and the degree of colonization of the gastric mucosa by the active and inactive form of Helicobacter pylori infection was analyzed in 50 patients with chronic non-atrophic gastritis, suffering from chronic constipation, and in 50 patients with chronic non-atrophic gastritis, who did not suffer from constipation. In the group of patients suffering from chronic constipation, the frequency of occurrence of the active form of Helicobacter pylori infection in different topographic zones of the stomach ranged from 46% to 56% with an average degree of mucosal seeding from 1.12 ± 0.13 (+) to 1.48 ± 0.13 (+), the frequency of occurrence of an inactive form of Helicobacter pylori infection in different topographic zones of the stomach ranged from 0% to 48% with an average degree of mucosal colonization from 0 ± 0.0 (+) to 1.30 ± 0.13 (+), while while in the group of patients who did not suffer from chronic constipation, the frequency of occurrence of an act distinct Helicobacter pylori infection in different topographic zones of the stomach ranged from 36% to 52% with an average degree of mucosal seeding from 1.02 ± 0.13 (+) to 1.34 ± 0.13 (+), and the frequency of occurrence of the inactive Helicobacter pylori infections in different topographic zones of the stomach ranged from 0% to 58% with an average degree of mucosal seeding from 0 ± 0.0 (+) to 1.56 ± 0.13 (+). In patients of the first group, the frequency of detection of intracellular "depots" of HP infection was 2.3 times higher than in patients of the second group.